Contemporary Literature on Islamic Economics: A Select Classified Bibliography of Works in English, Arabic and Urdu up to 1975 - Dr. Naveed Yazdani (Islamic Banking and Finance Review, 2014)
It is a book review on Contemporary Literature on Islamic Economics: A Select Classified Bibliography of Works in English, Arabic and Urdu up to 1975 Written By Muhammad Nejatullah Siddiqi,